Da produção de texto à produção de sentido : análise de textos produzidos a partir da orientação de um manual didático - Fonseca, Edwiges da (2015)
Analysing students’ texts in its sense production, this research aimed at raising discussions about the relationship between subject and text (Antunes, 2003, 2005 e 2009), just as well interpretation (Marcondes, 1994) and sense production (Abrahão, 2002, 2011 e Mari, 1991). Based on a enunciative perspective (Guimarães, 1999), the text is considered from its socio-historical conditions of production. Within the field of Applied Linguistics, this research had the objective of a view on the texts through the integral and systemic research-action (ISRA), taking into account the conditions of production of students in the last year of high school from a school in the slum. By analysing the use of the language in the texts, what was observed were subjects subsumed in their social conditions. With a writing style that shows great possibilities of organization and textual development, its language is intertwined with its anguishes while subjects rooted in their social universe. The condition of interpretation is restricted, therefore, to the imposed limitations by the pressure of the social conflict. In a broken and uneven language, the distance in relation with the writing demonstrates a situation of exclusion and detachment of a citizen life.